Microfacies and Depositional Environments of Miocene Isolated Carbonate Platforms from Central Luconia, Offshore Sarawak, Malaysia - Janjuhah, H.T. (Wiley-Blackwell Publishing Asia, 2017)
The Luconia Province – offshore Sarawak – is a key geological unit for understanding the distribution of hydrocarbon resources in Malaysia. Nevertheless, little effort has been made to address the palaeoenvironmental characteristics of the Tertiary carbonates in the key sector of Central Luconia. We study the sedimentology and petrography of core samples from a well in Central Luconia, for which thirteen microfacies have been identified reflecting different depositional settings. This is the first microfacies scheme elaborated for Luconian carbonates. Lithofacies and microfacies distribution are compatible with deposition in a reef complex, originating around a framework reef, within the euphotic zone. Sediments were deposited in environments of backreef, reef crest, and forereef. The fair weather wave base is marked by the presence of coralline red algae, foraminifera, decreasing degree of bioclast fragmentation and other microfacies features. As a result, a depositional-environmental model is constructed, depicting a reef complex built around a framework reef developed on the margin of an isolated platform. In addition, an innovative, preliminary time series analysis of facies, microfacies and depositional environment data reveal the existence of seasonal cycles in the stacking patterns of facies and microfacies. © 2017 Geological Society of China